1996
DOI: 10.1111/j.1365-4362.1996.tb01673.x
|View full text |Cite
|
Sign up to set email alerts
|

Successful Treatment of Vitiligo With Puva‐pigmented Autologous Epidermal Grafting

Abstract: This novel procedure is an excellent tool by which to treat segmental and localized vitiligo lesions that have failed to respond to other therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 25 publications
0
42
0
Order By: Relevance
“…In case of the full-thickness grafts, punch biopsies are taken at a distance of 1–5 mm from each other under local anaesthesia [1, 14]. For the blister technique, bullae can be induced manually with liquid nitrogen (3–6 freeze-thaw cycles for 3–5 s [13]) or with appropriately sized cups of sterilized disposable syringes at a sustained suction pressure of approximately 300 mm Hg for 30 min to 3 h [15]. The bullae can also be harvested using a specifically designed machine to generate suction blisters.…”
Section: Procedures For Harvesting Donor Skinmentioning
confidence: 99%
“…In case of the full-thickness grafts, punch biopsies are taken at a distance of 1–5 mm from each other under local anaesthesia [1, 14]. For the blister technique, bullae can be induced manually with liquid nitrogen (3–6 freeze-thaw cycles for 3–5 s [13]) or with appropriately sized cups of sterilized disposable syringes at a sustained suction pressure of approximately 300 mm Hg for 30 min to 3 h [15]. The bullae can also be harvested using a specifically designed machine to generate suction blisters.…”
Section: Procedures For Harvesting Donor Skinmentioning
confidence: 99%
“…(29)(30)(31) The repigmentation rate in these studies according to the review by Njoo et al was 87%, whereas Ozdemi et al reported rates between 25% -65%. (29)(30)(31)(32)(33)(34)(35)(36) In the study by Maleki et al, ten patients with refractory vitiligo who were treated by suction blister graft and subsequent PUVA therapy reported over 90% repigmentation in seven patients. In studies of blister grafting followed without phototherapy, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…(39) Scar formation, keloid, cobblestoning, sinking pits, thick margins and milia formation was much less compared to split thickness grafting or punch grafting. (33) …”
Section: Advantagesmentioning
confidence: 99%
“…Unfortunately failures are still anticipated in many cases. For better results, phototherapy or photochemotherapy of donor and recipient sites can also be performed before and after grafting [11,14,27]. The purpose of this work is to evaluate how effective suction blister grafts with concomitant phototherapy are in treatment of resistant vitiligo cases that had failed to respond to classic phototherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Because of these disappointing outcomes, several surgical methods were introduced in the hope of achieving a more encouraging response. Surgical techniques are reserved for patients with stable vitiligo that is unresponsive to conventional therapies [11][12][13][14]. A number of dermatosurgery techniques are available to promote repigmentation of vitiligo: mini-or punch grafts, split-thickness skin grafts, cultured epidermal sheets, cultured melanocyte suspensions, follicular grafts and suction blister epidermal grafts [15][16][17][18][19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%